ENT 300 : D’Florence Boutique / Nur Izzatie Sasha Musa ... [et al.] - Musa, Nur Izzatie Sasha; Mohamad Faudzai, Nursyahirah; Rosli, Siti Aishah; Ridzuan, Nurul Zalikha; Mohd Nazarrudin, Nur Faizah (2021)
D’Florence company is a partnership business. This company have five members which hold position as a General Manager, Administration Manager, Marketing Manager, Production and Operation Manager and Financial Manager. The business capital is amounted to RM50,000 where contribution of each member is RM10,000.00. D’Florence company is located at No. 6, Tingkat 1, Kompleks Amanjaya Mall, Jalan Jati, 08000 Sungai Petani, Kedah. The reasons why we choose Amanjaya Mall is because it is the main concentrated place by all the residents at that area. Our business company is a boutique which selling variety types of shawl, scarf and clothes. As we go thru with fashion, we provide fashion that suits the tastes of nowadays fashion. We have done many research about Malaysia trend fashion that will suitable with Malaysian people. Our target market is to all women that come with all income level and customer’s level of ages. We believe that we can able to achieve our goals and our future prospect which is introduce lots of new collection scarf and shawl that can attract hijab wear and plan to open more branches and expand our business in the Malaysia. We also believe that we can attract more people about fashion Muslimah that can popular in the eyes of world.